MIL-68(Al) and MIL-68(Fe) as broadband optical modulators for Q-switching fiber lasers operating at 2 and 2.9 μm - Zheng, Le; Sun, Fanxi; Zhou, Hongrong; Gao, Ang; Liu, Wenshu; Wang, Dongsheng; Wei, Chen; Liu, Yong (Frontiers in Physics, 2022)
We investigated 2 and 2.9 μm mid-infared fiber lasers passively Q-switched by MIL-68(Al) and MIL-68(Fe), which were fabricated via the hydrothermal method. The modulation depth of MIL-68(Al) was found to be 9.12% at 1.99 μm. And the modulation depths of MIL-68(Fe) were found to be 18.89% and 15.79% at 1.99 μm and 2.87 μm, respectively. We report Q-switching pulse generation in both Tm3+-doped and Ho3+/Pr3+ co-doped fiber lasers by using the as-prepared MIL-68(M, M = Al3+, Fe3+) as SAs. The center wavelengths were at 1.99 μm and 2.87 μm, respectively. These results indicate that MIL-68(M) has wideband nonlinear optical properties and promising application prospects in the field of optical modulators at 2- and 2.9-μm mid-infrared waveband. Work clearly accessible to a broad readership.